Determining the Climate Classes and Producing GIS-Based Climate Boundary Maps of Bartın Province - Hülya Keskin Çıtıroğlu; Deniz Arca (Doğal Afetler ve Çevre Dergisi)
Climate refers to the average of meteorological events and weather conditions observed over a long period of time for a region. Many scientists have made different climate classifications. The main goal in these classifications is to determine the similarities of the investigated environments by identifying climate types. Determining climate characteristics and understanding climate boundaries contribute to the sustainability of resources in the region and aid in the preparation of land use plans. It is clear that assessment the boundaries of various climate types to ensure sustainability of regional resources and land use plans. In this study, it was aimed to determine climate boundaries in order to prevent climate-related problems. For this purpose, in this study, the creation of the climate boundary maps of Bartın province (Amasra, Kurucaşile, Merkez District and Ulus) was taken as a basis, based on the need to form a basis for planning. For this reason, the water balance of each district station was calculated using measurement data from four meteorological stations located in the districts of Bartın province for the last thirty years, utilizing the Thornthwaite climate classification method. Additionally, climate types were determined using the Thornthwaite, Trewartha, Erinç, De Martonne, Köppen, and Trewartha climate classification methods. Then, Geographic Information System (GIS)-based climate boundary maps were produced by applying the Kriging interpolation method to the data associated with the location.